Health behaviour changes in partners of women with recent gestational diabetes: a phase IIa trial - Anne-Sophie Brazeau; Sara J. Meltzer; Romina Pace; Natasha Garfield; Ariane Godbout; Leslie Meissner; Elham Rahme; Deborah Da Costa; Kaberi Dasgupta (BMC, 2018)
Abstract Background We recently demonstrated that a gestational diabetes history in mothers is associated with higher postpartum incident diabetes not only in mothers but also in fathers. In the present study, we examined changes in health behaviours and cardiometabolic profiles in both mothers and partners who participated in a diabetes prevention program within 5 years of a gestational diabetes pregnancy. Methods Couples were enrolled into a 13-week program that included 5 half-day group sessions and web/telephone-based support between sessions. It was designed in consultation with patients and previously studied in mothers. We computed mean changes from baseline (95% CI) for physical activity, eating, and sleep measures, and cardiometabolic parameters (fasting and 2-h post glucose load plasma glucose, BMI, blood pressure) in both partners and mothers. Results Among 59 couples enrolled, 45 partners (76%) and 47 mothers (80%) completed final evaluations. Baseline cardiometabolic measures averaged within normal limits. Similar to mothers, partners increased physical activity (+ 1645 steps/day, 95%CI 730, 2561; accelerometer assessed moderate-to-vigorous physical activity + 36.4 min/week, 95% CI 1.4, 71.4) and sleep duration (+ 0.5 h/night, 95% CI 0.1, 0.9) and reduced the sodium-to-potassium ratio of food intake (− 0.09 95% CI -0.19, − 0.001). No conclusive changes were observed in glucose measures or insulin resistance; in analyses combining mothers and partners, systolic blood pressure decreased (− 2.7 mmHg, 95% CI -4.4, − 1.0). Conclusions Partners and mothers demonstrated improved physical activity, sleep, and dietary quality. Baseline cardiometabolic profiles averaged at normal values and there were no changes in glucose or insulin resistance; some blood pressure impact was observed. While strategies need to be developed to attract participants at higher cardiometabolic risk, this study demonstrates that partners of women within 5 years of a gestational diabetes diagnosis can be recruited and do achieve health behaviour change. Trial registration ClinicalTrials.gov: NCT02343354 (date of registration: January 22, 2015).